Factors Affecting People’s Participation in Conservation of Common Property Resources in JFMCs of Himachal Pradesh - Brahmi, M. K.; Sehgal, R. N. (Indian Forester, 2008)
Four Forest Divisions were selected from four districts of Himachal Pradesh representing different agro-climatic zones. The Common Property Resources (CPRs) of the study area included forests, village common lands, panchayat lands, ponds, irrigation water channels (kuhl), bowari, village paths, temple and river banks. Different incentives were given to the people for the conservation of these resources. In total, 12 factors were identified in all the Forest Divisions under study, responsible for poor participation of the local people. The prime factor which influenced the people’s participation according to their importance are: lack of awareness and knowledge about CPRs, lack of training and visit programme, poor economic status, self interest of people, low land holding, illiteracy in aged groups, village politics, lack of interest in money contribution, prevailing perception for getting subsidy from government programmes, lack of transparency in the project activities, lack of coordination with staff and local people and improper usufruct sharing (in descending order of rank distribution). Policy and development emphasis on these factors would increase the participation in the similar projects.